The English - Halifah Pagarra; Rachmawaty; Musawira; Handayani, Besti; Syaiful Haq, Muhammad Naufal (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Matoa (Pometia pinnata) is a plant commonly used by the Indonesian people for traditional medicine due to its rich content of metabolites. This study aimed to analyze the phytochemical composition and antibacterial activity of matoa leaves The leaves were extracted using a 70% ethanol solvent with a ratio of 1:4 using the maceration method, and phytochemical screening was performed on the leaf extract. The antibacterial activity was tested against Staphylococcus aureus and Escherichia coli using the disc diffusion method. The results indicated that the matoa leaf extract contains various metabolites, including triterpenoids, steroids, flavonoids, phenolics, saponins, tannins, and alkaloids. Secondary metabolite compounds in matoa leaves are thought to be able to inhibit microbial growth so that inhibition zones can be formed. Furthermore, the antibacterial activity demonstrated that the matoa leaf extract effectively inhibited the growth of S. aureus and E. coli. the largest inhibition zone is of 18.22 mm at 10% extract concentration, and E. coli, with an inhibition zone largest is of 10.87 mm at 10% extract concentration. While the smallest inhibition zone in S. aureus is 15.29 mm at 7.5% concentration, and in E. coli is 5% at 5% extract concentration.. This study suggests that matoa leaves have the potential to serve as natural bioactive compounds and antimicrobial agents in the clinical industry. Keywords: Matoa, Phytochemical, Antibacterial activity, Staphylococcus aureus, Escherichia coli